The Power of English Music to Improve Students' Listening Skills - Roudhotun Nadiyya; Suryadi Suryadi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study looked at the effectiveness of using English music as a learning tool to improve listening skills in a group of 132 students. Snowball sampling was used to select a sample of 54 students. This research uses a quantitative research methodology, with two groups: an experimental group that uses English songs as a learning tool, and a control group that uses traditional teaching methods. This research should explain how English songs can improve students' listening skills. In addition, this research seeks to understand the causes of students' poor listening skills so that appropriate treatment can be implemented in the classroom. The research results revealed a significant positive impact on students' listening skills when learning through English songs. This method substantially improved the listening skills of the experimental group. This research shows that incorporating songs and lyrics into the classroom is the most effective method for improving students' listening skills. These positive results were caused by good student responses and improved listening comprehension skills. In conclusion, this study advocates the integration of English music into language education as a powerful tool for developing listening skills. Positive feedback from students and demonstrated improvements in listening comprehension underscore the effectiveness of this innovative pedagogical approach. This research provides valuable insights for language educators and curriculum developers seeking innovative and engaging methods to improve language acquisition.